Case report: Successful thromboprophylaxis with enoxaparin in a pregnant woman with internal jugular vein agenesis - Di Micco, Pierpaolo; Orlando, Luana; Cataldo, Donato; Imbalzano, Egidio (Frontiers in Medicine, 2022)
Internal jugular agenesis is a vascular malformation that can be associated to history of recurrent headache and that may be complicated by neurological dysfunction as intracranial hypertension, intracranial micro thromboses, neurodegenerative diseases as multiple sclerosis because an abnormal intracranial venous drainage. Data on thromboprophylaxis of pregnant women with this vascular anomaly are still deficient in the literature. The simultaneous presence of jugular vein agenesis and thrombosis may be possible in cases of acute illness, hormonal treatment, pregnancy, hypomobility, or in cases of venous drainage abnormalities (VDA) (e.g., May Turner syndrome). So, we here report our positive experience with a patient carrier of internal jugular agenesis during pregnancy using thromboprophylaxis with enoxaparin.